Experiences and Perceptions of Black Men Who Have Sex with Men About Acquiring HIV: A Qualitative Narrative Perspective. (September 2018) - Nation, Austin; Waters, Catherine M.; Dawson‐Rose, Carol
Abstract : N/A: In the United States, Black men who have sex with men (MSM), between the ages of 18 and 34 years, have the highest rates of new HIV infections. The prevalence of HIV in this population is three to four times higher than their White MSM counterparts. Twelve Black MSM from the Bay Area, nine with HIV and three without HIV, were interviewed regarding their experiences and perceived risks of acquiring HIV. Narrative analysis revealed these themes: (a) tested regularly for HIV, (b) HIV knowledge varied before arriving in San Francisco, (c) condom use typically nonexistent when under the influence of alcohol and other drugs, (d) inability to negotiate sex and condom usage, and (e) sense of anticipation, resignation, and acceptance about acquiring HIV. Implications of this study highlight the need for Black MSM to have earlier HIV prevention education, including condom negotiation skills, particularly when under the influence of drugs and/or alcohol.